Function and expression of renal organic anion transporters in experimental diabetes in mice - Anusorn Lungkaphin (2018)
The renal clearance of organic anions (OAs) is mediated by organic anion transporters (Oats) located at the renal proximal tubules (RPTs). Decreased elimination of OAs or anionic drugs may result in severe nephrotoxicity. Up to now, no study dealt with the consequences of diabetes mellitus on renal anion transport function. This study was conducted to examine renal Oat expression and function in diabetic mice induced by streptozotocin. Transport activity was determined by measuring the uptake of fluorescein into isolated RPTs. Diabetic mice demonstrated an increase in plasma glucose, triglyceride, and growth retardation. A decrease in fluorescein accumulation in RPTs was observed in mice only after 28 and 42 days of diabetes. There was also a concomitant reduction in the level of kidney cortex membrane Oat3, but not Oat1. These results indicate that renal anion transport function is impaired after a prolonged (four weeks or longer) diabetic condition.